Household air pollution and urinary incontinence symptoms among older adults in LASI: a large-scale population-based study - Xiaoyang Liu; Kai Ma; Shengzhuo Liu; Pan Song; Luchen Yang; Zhenghuan Liu; Jing Zhou; Linchun Wang; Xin Yan; Yunfei Yu; Qiang Dong (BMC, 2024)
Abstract Background The effects of household air pollution on urinary incontinence (UI) symptoms and stress urinary incontinence (SUI) symptoms have not been studied. This study seeks to investigate the correlation between household air pollution and UI/SUI symptoms among middle-aged and elderly adults in India. Methods We employed data derived from individuals aged 45 years and older who participated in the inaugural wave (2017-2018) of the Longitudinal Aging Study in India (LASI). The assessment of household air pollution exposure and the occurrence of UI/SUI symptoms relied on self-reported data. The analytical approach adopted was cross-sectional in nature and encompassed a cohort of 64,398 participants. To explore relationships, we utilized multivariate logistic regression analysis, incorporating subgroup analysis and interaction tests. Results 1,671 (2.59%) participants reported UI symptoms and 4,862 (7.55%) participants reported SUI symptoms. Also, the prevalence of UI/SUI symptoms is much higher among middle-aged and elderly adults who use solid polluting fuels (UI: 51.23% vs. 48.77%; SUI: 54.50% vs. 45.50%). The results revealed a noteworthy correlation between household air pollution and the probability of experiencing UI/SUI symptoms, persisting even after adjusting for all conceivable confounding variables (UI: OR = 1.552, 95% CI: 1.377-1.749, p < 0.00001; SUI: OR: 1.459, 95% CI: 1.357-1.568, p < 0.00001). Moreover, significant interaction effects were discerned for age, education level, tobacco consumption, alcohol consumption, and physical activity (p for interaction < 0.05). Conclusions The results of our study indicate that the utilization of solid fuels in the home increases the likelihood of developing urinary incontinence and stress urinary incontinence. As a result, we argue that there is an immediate need to reform the composition of cooking fuel and raise public awareness about the adverse effects of air pollution in the home.